2019
DOI: 10.30802/aalas-jaalas-19-000032
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Intramuscular Meloxicam in Zebra Finches (Taeniopygia guttata)

Abstract: Zebra finches (Taeniopygia guttata) are songbirds that often undergo surgical procedures as part of research into learning and memory; these surgeries include those for intracranial injections and cranial implants. At our institution, birds receive subcutaneous lidocaine (a local anesthetic) and intramuscular buprenorphine (an opioid analgesic) preoperatively, with buprenorphine continued every 12 h postoperatively for 2 to 3 d. More recently, the possibility of substituting meloxicam (a COX2-selective NSAID) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…However, the obvious differences in t 1/2ʎz of MLX, CRP, and TA have been reported among species. After IM and oral administration in quails, the t 1/2ʎz of MLX was 1.55 and 1.59 h, respectively, which was similar to that previously reported in flamingos (oral: 1.83 h, Lindemann et al, 2016), shorter than that previously reported in parrots (IM: 15.1-35.3 h, oral: 15.8-33.6 h, Molter et al, 2013;Montesinos et al, 2016), penguins (IM: 31.87 h, oral: 28.59 h, Morrison et al, 2018), zebra finches (IM: 3.24 h, Miller et al, 2019), hawks (oral: 3.97 h), owls (oral: 5.07 h, Lacasse et al, 2013), and geese (oral: 3.65 h; Sartini et al, 2020), and longer than that previously reported in cockatiels (oral: 0.90 h, Dhondt et al, 2017) and vultures (IM: 0.42 h, oral: 0.32 h, Naidoo et al, 2008). After IM and oral administration in quails, the t 1/2ʎz of TA was 1.51 and 1.25 h, respectively, which was shorter than that previously reported in mammals (IM: 2.61-8.22 h, oral: 5.13-19.7, Corum et al, 2018;Sidhu et al, 2005;Sidhu et al, 2006;Dinakaran & Dumka, 2013) and reptiles (IM: 22.49-53.69 h, Corum et al, 2019a;Raweewan et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the obvious differences in t 1/2ʎz of MLX, CRP, and TA have been reported among species. After IM and oral administration in quails, the t 1/2ʎz of MLX was 1.55 and 1.59 h, respectively, which was similar to that previously reported in flamingos (oral: 1.83 h, Lindemann et al, 2016), shorter than that previously reported in parrots (IM: 15.1-35.3 h, oral: 15.8-33.6 h, Molter et al, 2013;Montesinos et al, 2016), penguins (IM: 31.87 h, oral: 28.59 h, Morrison et al, 2018), zebra finches (IM: 3.24 h, Miller et al, 2019), hawks (oral: 3.97 h), owls (oral: 5.07 h, Lacasse et al, 2013), and geese (oral: 3.65 h; Sartini et al, 2020), and longer than that previously reported in cockatiels (oral: 0.90 h, Dhondt et al, 2017) and vultures (IM: 0.42 h, oral: 0.32 h, Naidoo et al, 2008). After IM and oral administration in quails, the t 1/2ʎz of TA was 1.51 and 1.25 h, respectively, which was shorter than that previously reported in mammals (IM: 2.61-8.22 h, oral: 5.13-19.7, Corum et al, 2018;Sidhu et al, 2005;Sidhu et al, 2006;Dinakaran & Dumka, 2013) and reptiles (IM: 22.49-53.69 h, Corum et al, 2019a;Raweewan et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…After IM administration of MLX at a dose of 1 mg/kg in quails, the C max (4.27 μg/mL), and T max (0.33 h) were lower and shorter, respectively, than those previously reported in parrots (C max : 8.32-10.5 μg/mL, T max : 0.5-1.4 h) and zebra finches (C max : 8.56 μg/mL, T max : 0.5 h) (Miller et al, 2019;Molter et al, 2013;Montesinos et al, 2016). The C max varied from 0.1 to 10.84 μg/mL and T max from 0.5 to 13.2 h after the oral administration of MLX to different bird species (parrots, penguins, cockatiels, and flamingos) at a dose of 1 mg/ kg (Dhondt et al, 2017;Lindemann et al, 2016;Molter et al, 2013;Montesinos et al, 2016;Morrison et al, 2018).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Meloxicam elimination was also fast in the undulate skates, with a relatively short t 1/2 β (3.55 h) when compared to other mammalian species, such as rabbits (6.1 h) or horses (8.5 h) [ 14 , 27 ]. The elimination half-life was, however, within range of that reported in teleost species, such as tilapia (1.59 h) and trout (4.55 h), reptile species, such as the loggerhead sea turtle ( Caretta caretta Linnaeus, 1758) (3.26 h), and avian species, such as the zebra finch ( Taeniopygia guttata Vieillot, 1817) (3.24 h) [ 12 , 14 , 28 , 29 ]. Previous studies performed with meloxicam in avian species showed that interspecific and interindividual variations in Phase I system enzymes, such as cytochromes P450 (CYPs), can result in longer half-lives of metabolized NSAIDs [ 7 ].…”
Section: Discussionmentioning
confidence: 56%